Effects of Diets Enriched in Linseed and Fish Oil on the Expression Pattern of Toll-Like Receptors 4 and Proinflammatory Cytokines on Gonadal Axis and Reproductive Organs in Rabbit Buck. (22nd January 2020) - Menchetti, Laura; Barbato, Olimpia; Sforna, Monica; Vigo, Daniele; Mattioli, Simona; Curone, Giulio; Tecilla, Marco; Riva, Federica; Brecchia, Gabriele
Abstract : Infections of the genital tract can perturb the fertility in humans and animals. Pathogen recognition and activation of innate immunity onset through the pattern recognition receptor activation, such as Toll-like receptor 4 (TLR4), leading to the production of proinflammatory cytokines and mediators. TLR4 is expressed both on leukocytes and nonimmune cells. Rabbit TLR4 shows great similarity to its human counterpart. Moreover, the TLR4 signalling pathway could be modulated by long-chain polyunsaturated fatty acids (LC-PUFA). The objectives of this study were (i) to determine the expression levels of TLR4 and proinflammatory cytokines in the reproductive hypothalamic-gonadal axis of the male rabbit and (ii) to evaluate if the n-3 PUFA-enriched diets can modify their expression levels in the tissues and LC-PUFA profiles in seminal plasma. Fifteen rabbit bucks (n = 5 /experimental group) were fed with different diets: commercial standard (group C), rich in extruded linseed (10%, group L), and in fish oil (3%, group FO) for 110 days. TLR4, TNF- α, and IL-1 β mRNA were ubiquitously expressed throughout the hypothalamic-gonadal axis. However, TLR4 mRNA expression was lower in the hypothalamus than the epididymis (P < 0.01 ), seminal vesicles (P < 0.01 ), and pituitary gland (P < 0.05 ). Dietary enrichment in PUFA did not modify the gene expression profile nor the histological characteristics of the tissues. Conversely in seminal plasma, rabbits fed with L and FO had lower n-6 (P < 0.05 ), LC-PUFA n-6 (P < 0.05 ), and n-6/n-3 ratio (P < 0.05 ) but higher n-3 (P < 0.001 ) and LC-PUFA n-3 (P < 0.01 ) compared to the control group. Our study builds a map of the gene expression of TRL4 and proinflammatory cytokines in the reproductive hypothalamic-gonadal axis of the male rabbit, fundamental step for understanding the immune defence mechanisms. Diets enriched in LC-PUFA did not affect basal gene expression but modulated sperm fatty acid composition. Finally, rabbit may be an excellent animal model to study the relationship between inflammation and infertility, and the nutritional modulation of immune functions.